PENGARUH TENAGA KERJA DAN UPAH EKONOMI KREATIF TERHADAP PDB - Nabila, Alifia; Muljaningsih, Sri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research aims to analyze (1) the influence of the number of workers in the creative economy sector on Indonesia's GDP; (2) the influence of labor wages in the creative economy sector on Indonesia's GDP; (3) the influence of the number of workers and wages in the creative economy sector on Indonesia's GDP. The research method used in this research is quantitative associative relationships between two or more variables. The data used is data that has been processed from the results of the National Labor Force Survey of the Central Statistics Agency in the Report of the Ministry of Tourism and Creative Economy of the Republic of Indonesia, as well as GDP data in Indonesia from 2018-2021. The data analysis method used in this research is panel data regression which consists of model selection tests, classical assumption tests, and hypothesis tests. Based on the research results, it shows that (1) creative economy workers have an effect on gross domestic product (2) wages for creative economy workers have no effect on gross domestic product (3) creative economy workers and wages have a simultaneous effect on gross domestic product.